LITERATURE REVIEW: ADJOINT-BASED COMPUTATIONAL FLUID DYNAMICS FOR INDIVIDUALIZED SEPTOPLASTY PLANNING IN NASAL SEPTUM DEVIATION - Das Sharodiya; Norjigitov Firdavs Nordirjonovich (PEDAGOGS, 2025)
Abstract: Nasal septum deviation (NSD) is common anatomical pathology leading to nasal airway obstruction and reduced quality of life. Despite the accepted corrective surgery being septoplasty, postoperative outcomes remain unpredictable. Traditional surgical planning often depends on anatomical assessment and surgeon experience rather than necessarily accurately predicting airflow improvement. Recent progress in computational fluid dynamics (CFD), specifically adjoint-based optimization techniques, has brought about a paradigm shift toward customized septoplasty planning. In this review article, critically appraising the state-of-the-art in the literature regarding adjoint-based CFD techniques being utilized in the management of NSD, their ability to customize surgical interventions based on individual patient-specific airflow dynamics is emphasized. The existing clinical literature, computational methods, benefits, drawbacks, and future directions of incorporating these technologies into clinical routine are explored[1].